The Effect of Gelatin from Different Fish Skin on Physical and Sensory Characteristics of Marsmallow - Izmy Nur Aziza; Yudhomenggolo Sastro Darmanto; Retno Ayu Kurniasih (Jurnal Perikanan Universitas Gadjah Mada, 2019)
Gelatin is one type of protein obtained from partial hydrolysis of natural collagen. Utilization of gelatin has been widely applied to food, especially in foods related to elastic texture, for example marshmallow. The purpose of this research was to determine the quality of various types of gelatin based on gel strength, elsticity, water content, hedonic and to know the best marshmallow. The experimental design was complete randomized design. The treatment was different fish skin gelatin, namely patin, payus, and cobia with concentration of 7.39%. The parameters consisted of gelatin tests (yield, gel strength, viscosity) and marshmallow tests (gel strength, elasticity, water content and hedonic). Parametric data were analyzed with Analysis of Varience test and continued with Honestly Significant Difference test. The results showed that the use of different skin had significantly different (P<0.05) on yield, gel strength and viscosity, with the result of patin (13.24%, 280.56 bloom, 2.05 cP), payus (15.47%, 328 bloom, 3.18 cP), cobia 17.88%, 392.24 bloom, 5.63, respectively. The use of gelatin from payus and cobia had significantly different (P<0.05) to marshmallow characteristic. Marshmallow with gelatin skin of cobia fish had gel strength 1564.19 g.cm, elasticity 95.16 mm, water content 14.41% and hedonic test with interval of of 7.52 < μ < 7.91 which was means liked by panelists.